Салтовское гончарное производство (по материалам ремесленного центра в урочище Роганина) - Колода, В.В. (Степи Европы в эпоху средневековья, 2001)
The article is dedicated to the analysis of the remains of pottery production, revealed in one of the trade centres of the Saltov-Mayatsky archaeological culture in the Kharkov region. The paper gives a description of four previously unknown types of potter’s furnaces which were found there. The centre manufactured kitchen pots on a mass scale. According to their capacity the vessels can be divided into three groups: those with the capacity of 0.5-0.65 litres, the ones with the capacity of 2.4-3.4 litres, and those with the capacity of 7-8 litres. The trade centre was the place of season work for both potters and iron -melting artisans in the IXth c. A.D.